Factors that influence buying houses for consumers - Hartina Beddu; Hayun Abdul; Baharuddin Semmaila; Munawir Nasir; Sitti Hajar (Jurnal Manajemen Bisnis, 2021)
This study aims to examine the influence of family, economic and lifestyle factors on consumer decisions. This research was conducted at the Royal Spring Housing, located in Gowa Regency. The population chosen is all home consumers at the Royal Spring Housing PT. Buana Sentosa Asri in Makassar. The number of samples is calculated using the Slovin formula, and the number of samples to be studied is 82 household samples and is determined by simple random sampling. Data collection was carried out by distributing questionnaires to all respondents. The analysis tool uses multiple linear regression. The results of the study found that family factors, economic factors, and lifestyle have a positive and significant effect on consumer decisions.